2022
DOI: 10.3390/plants11030448
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Magnoliaceae Plastomes: Adding Neotropical Magnolia to the Discussion

Abstract: Chloroplast genomes are considered to be highly conserved. Nevertheless, differences in their sequences are an important source of phylogenetically informative data. Chloroplast genomes are increasingly applied in evolutionary studies of angiosperms, including Magnoliaceae. Recent studies have focused on resolving the previously debated classification of the family using a phylogenomic approach and chloroplast genome data. However, most Neotropical clades and recently described species have not yet been includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
3
1
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 115 publications
2
3
1
3
Order By: Relevance
“…Highly variable regions provide abundant phylogenetic information and can be used as potential molecular markers to delimit closely related taxa [ 55 ]. The Pi of highly variable regions within subgenus Gynopodium species was lower (< 0.008) compared with previously published values of other species [ 56 , 57 ] and some of Magnolia species [ 29 , 30 ]. The low genetic diversity of subgenus Gynopodium species and other Magnolia species, e.g., Magnolia ashei may relate to their limited habitat and small populations as threatened species [ 54 , 58 , 59 ].…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…Highly variable regions provide abundant phylogenetic information and can be used as potential molecular markers to delimit closely related taxa [ 55 ]. The Pi of highly variable regions within subgenus Gynopodium species was lower (< 0.008) compared with previously published values of other species [ 56 , 57 ] and some of Magnolia species [ 29 , 30 ]. The low genetic diversity of subgenus Gynopodium species and other Magnolia species, e.g., Magnolia ashei may relate to their limited habitat and small populations as threatened species [ 54 , 58 , 59 ].…”
Section: Discussioncontrasting
confidence: 73%
“…Our results indicated that the CPGs of six subgenus Gynopodium species are similar in size (ca. 160 kb) and structure (quadripartite circular structure) to other Magnolia species [ 28 – 30 ] as well as other higher plants [ 31 ]. The total number, order, and composition of genes in the CPGs were highly conserved within subgenus Gynopodium , which is also consistent with most Magnolia species [ 32 , 33 ], suggesting a very conserved structure of CPGs of subgenus Gynopodium .…”
Section: Discussionmentioning
confidence: 99%
“…However, such an expansion is small, and no important expansions or contractions were observed in these cp sequences. This result is similar to the expansion of the chloroplast genomes of other Magnoliaceae species in the IR region [ 30 ], but different from the contraction of Zingiberaceae and Arecaceae [ 31 , 32 ]. This indicates that different species have evolved under the influence of different factors, resulting in different degrees of expansion and contraction of IR/SC boundaries, thus showing the diversity in genome length and boundaries [ 33 ].…”
Section: Discussionsupporting
confidence: 61%
“…The plastome of five new sequences of Manglietia ranges from 157,093 bp (M. calcarea2) to 160,493 bp (M. kwangtungensis). It is similar in size to the plastomes of other previously published Magnoliaceae species [21,90]. The genome size of M. calcarea2 is approximately 3000 bp shorter than that of the other two samples, primarily due to a loss in the IR region encompassing the rrn16-trnI-GAU sequence.…”
Section: Plastome Variationsupporting
confidence: 67%